Grow green between building - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Urban Agriculture: Growing Vegetables in Cities By J Boland, Agromisa CTA co-publication, Agrodok Series, 2002. 84 pp. ISBN 90 77073 25 6 CTA number 1087. 5 credit points